2012
DOI: 10.1080/08098131.2011.571278
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy as procedural support for invasive medical procedures: toward the development of music therapy theory

Abstract: In partial response to the demand for evidence-based practice, there is an increasing interest in the use of music therapy as procedural support for both invasive and non-invasive medical procedures. Clinicians and researchers are attempting to define how music therapy functions as procedural support in order to advance clinical practice and research, but concepts remain inadequately specified in the literature. The current philosophical inquiry used qualitative document analysis to critically examine the exta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…For patients with special needs, several visits with a music therapist may be needed to build a trust relationship and to have multiple opportunities for practice of the music‐based skills. On the day of the treatment, it is recommended that the music therapist works with the patient prior to the dental procedure and continue to offer a calming or engaging experience upon arrival of the dental practitioner to prevent escalation of anxiety at the start of treatment (Ghetti, ).…”
Section: Music Therapy For Highly Anxious Patientsmentioning
confidence: 99%
“…For patients with special needs, several visits with a music therapist may be needed to build a trust relationship and to have multiple opportunities for practice of the music‐based skills. On the day of the treatment, it is recommended that the music therapist works with the patient prior to the dental procedure and continue to offer a calming or engaging experience upon arrival of the dental practitioner to prevent escalation of anxiety at the start of treatment (Ghetti, ).…”
Section: Music Therapy For Highly Anxious Patientsmentioning
confidence: 99%
“…She also underlines the importance of individualised treatment, which has to be reflected in the development of intervention protocols. 2 In turn, Ghetti's (2012) article about music therapy as support in invasive medical procedures is also influenced by the neuromatrix model. Ghetti presents and summarises key concepts in a theoretical transaction model ( Figure 2).…”
Section: Theoretical Rationalementioning
confidence: 99%
“…Implementation of the music therapy intervention, consisting of therapist + music + patient responses, adds another three lenses to the experience through which biological, psychological and/or social positive influences can be viewed. Ghetti (2012) points to three primary approaches of music therapy as procedural support: music alternate engagement (refocusing), integration and music-assisted relaxation. The current protocol focusses on musicassisted relaxation within the framework of short-term treatment, thus operating at an augmentative or supportive level (Bruscia, 2014;Dileo, 2015Dileo, , 2016.…”
Section: Theoretical Rationalementioning
confidence: 99%
“…The Gate Control Theory of pain (Melzack and Wall 1965) proposes that an auditory stimulus, such as music, acts to divert attention away from the experience of pain, by activating different areas of the brain required for processing auditory information. In a review of research studies of music therapy as procedural support for invasive medical procedures, Ghetti (2012) found that the Gate Control theory was the most commonly mentioned theory in these studies, although Melzack and Katz' (2004) theory of the body-self neuromatrix goes further to address the inter-related areas of the brain that are involved in pain perception and pain behavior. Ghetti (2012) stated that:…”
Section: Theoretical Framework In Music-assisted Relaxation Researchmentioning
confidence: 99%
“…In a review of research studies of music therapy as procedural support for invasive medical procedures, Ghetti (2012) found that the Gate Control theory was the most commonly mentioned theory in these studies, although Melzack and Katz' (2004) theory of the body-self neuromatrix goes further to address the inter-related areas of the brain that are involved in pain perception and pain behavior. Ghetti (2012) stated that:…”
Section: Theoretical Framework In Music-assisted Relaxation Researchmentioning
confidence: 99%